An effective biodegradable curcumin loaded magnetic microsphere: Applications for drug delivery and cancer treatment - Selvaraj Esthar; Jegathalaprathaban Rajesh; Natarajan Prakash; Srinivasan Ayyanaar; R. Bhaskar; Sundaram Thanigaivel; Thomas J. Webster; Gurusamy Rajagopal (Elsevier, 2023)
Introduction: The non-specific delivery of drugs to tissues is one of the major problems in traditional chemotherapy that creates problems, importantly cytotoxicity to healthy cells. A drug carrier can be designed and synthesized using a variety of techniques that allow the drug to be delivered to a specific target site with sustained release. Here, we designed novel polymer-encapsulated magnetic microspheres as drug carriers that enable site-specific and controlled drug delivery to improve therapeutic outcomes. In our study, we developed a novel emulsion-based technique to produce curcumin-loaded polymer-encapsulated magnetic microspheres. Methods: The method involves the preparation of a binary emulsion system (water-in-oil-in-water (W1-O-W2) followed by evaporation of the continuous aqueous phase to produce magnetic polylactic acid (PLA) microspheres containing curcumin (CUR) and ferrite magnetic nanoparticles (FA-MMS). The construction of the prepared Ferrite@FA-CUR-PLA-MMS drug carrier was characterized using various spectroscopic and microscopic techniques. Results: The prepared Ferrite@FA-CUR-PLA-MMS drug displayed a unique and constant pH-dependent curcumin release from the drug carriers. The cytotoxicity determination of the Ferrite@FA-CUR-PLA-MMS drug by MTT assays confirmed a low cytotoxic effect on A549 and Hela cancer cells with a minimum inhibitory concentration (IC50) for A549 cells at 15 µg/ml for 24 h and for Hela cells, the IC50 value was 12 µg/ml. After 24 h, the IC50 values for A549 and Hela cancer cells were found to be 10.2 µg/ml and 8.8 µg/ml, respectively. After 10 days of incubation, the drug exhibited total destruction of the A549 and Hela cancer cells. Discussion: Our findings have greater implications for the potential use of magnetic nanoparticles in cancer chemotherapy. Further investigations on the application of this drug delivery system could be extended to the site-specific and controlled delivery of other cancer chemotherapeutic agents.